The Human Mental Transcending Ability as a Coping and Life-Expanding Resource - Borgen, Berit (Journal of spirituality in mental health, 2018)
The aim in this study is to shed light on the human mental ability to transcend the experience of problematic situations and disruptive apprehensions. This might expand the possibility to create new adaptive problem-solving potentialities in actual life situations. Thereby it can potentially have a significant impact on the processes of promoting recovery from mental disorders and mental liberation generally. Transcending spiritual experiences might elicit transformational turning points, which might occur in religious and/or in nonreligious contexts. This is exemplified in the article by cases that are discussed related to relevant theories. The research material was obtained with qualitative research methods.